An improved regioselective preparation of methyl 2,3-di-O-acetyl-α, β-d-xylofuranoside - Gudiño, Esteban Dario (2012)
Methyl 2,3-di-O-acetyl-α,β-d-xylofuranoside was prepared as the sole regioisomer in 6372% yield, according to the applied mass of substrate, through a Candida antarctica lipase B catalysed alcoholysis of methyl 2,3,5-tri-O-acetyl-α,β-d-xylofuranoside. The product is a potential synthetic precursor for 5-modified xylofuranosides and 5′-modified xylonucleosides.